Chemical constituents and anti-neuroblastoma activity from Boesenbergia stenophylla - Phoebe Sussana Primus,; Muhammad Hazran Ismail,; Nabila Elyana Adnan,; Wu, Carol Hsin-Yi; Kao, Chai-Lin; Choo, Yeun-Mun (Penerbit Universiti Kebangsaan Malaysia, 2022)
Three diarylheptanoids and one flavonoid, i.e. 7-(4-hydroxy-3-methoxyphenyl)-1-phenylhept-4-en-3-one (4), 5R-hydroxy-7-(4-hydroxy-3-methoxyphenyl)-1-phenylheptan-3-one (5), 1,7-diphenylhept-4-en-3-one (6), and 3,5,7-trihydroxyflavone (7) were isolated and characterized from the rhizome of Boesenbergia stenophylla. Compounds 2 and 4 displayed excellent anti-neuroblastoma activity which reduces the cell viability to 30% and 20%, respectively. The results from the molecular docking experiments targeting the protein kinases regulating neuroblastoma cell survival (PI3K/AKT1 signalling pathway) are consistent with that of the in vitro results. Finally, the structures of 4-7 were elucidated using spectroscopic methods (UV, IR, NMR, and HRESIMS).